Saberes docentes e a inclusão de alunos com transtorno do espectro autista: um estudo a partir da narrativa de professoras que atuam no atendimento educacional especializado das escolas municipais de Boa Vista/RR - Costa, Aline Fernandes (2023)
The school inclusion of students with Autistic Spectrum Disorder is a very tolerant reality in Brazil and in the world. Both in public and private schools, the presence of target audience of Special Education students, among them, children with Autistic Spectrum Disorder is noted, however, the offer of a teaching that guarantees the participation and learning of these children still is under construction. In this perspective, the study aimed to understand how the teachers of the Specialized Educational Service of the municipal network of Boa Vista/RR have built knowledge to work in the teaching of children with Autistic Spectrum Disorder. The methodology of the study is a qualitative approach of the participatory type, moreover, it is situated within the scope of (Self) Biographical Research in Education, using the narrative interview as an investigation method. The research was carried out with three teachers who attend the Specialized Educational Service of Municipal Elementary Schools in Boa Vista/RR. The corpus used for analysis consists of four written narratives, one of which, the author's, collected in the year 2022. We relied on express studies in the area to define the "training axes", which served as a "guide" in the narrative writing process. The procedure used to interpret the data contained in the narratives constructed by the subject teachers of this research, was based on the analysis from a three-dimensional model, in which the analysis considers three elements: interaction, continuity and situation. The narratives indicate that the knowledge constructed by the teachers when teaching children with ASD comes from experience and exchange relationships between professionals who work in the same role. In addition, it was possible to perceive in the narratives of the teachers a great influence of teacher trainers and people with disabilities within the family as a reason for choosing and directing to this space of action. It was also inferred the need for continuing education that takes into account the specificities of teaching work. The inheritance of this study for the scientific community and the directions for new studies that are also aimed at understanding how the construction of knowledge for performance in regular teaching rooms has been taking place.